Centralised Lithuanian Language and Literature Assessments of Secondary School Students: Population Analysis - Želvys, Rimantas; Raižienė, Saulė; Vaitekaitis, Jogaila; Dukynaitė, Rita; Jakaitienė, Audronė (Pedagogika, 2023)
The aim is to analyse assessments of Lithuanian language and literature for the entire secondary school student population focusing on gender comparison, and development of models for the prediction of achievements. We use the results of the 10th grade test for the period 2011–2015 and the same cohorts in the Matura exam. Gender differences are observed in analysed national centralized assessments. The distribution of the 10th grade test achievements resembles the bell-shaped curve, whereas the Matura – do not.